2010
DOI: 10.1021/ac9022605
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric Detection of Dopamine in Vivo with an Enzyme Based Carbon Fiber Microbiosensor

Abstract: We developed a novel implantable enzyme-based carbon fiber biosensor for in vivo monitoring of dopamine. The biosensor is fabricated using tyrosinase immobilized in a biocompatible matrix consisting of a biopolymer, chitosan and ceria-based metal oxides, deposited onto the surface of a carbon fiber microelectrode with a diameter of approximately 100 microm. Tyrosinase catalyzes the conversion of dopamine to o-dopaquinone, and the reduction of o-dopaquinone, which requires a low potential difference, was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
177
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(179 citation statements)
references
References 51 publications
1
177
1
Order By: Relevance
“…Therefore, it was believed that the increased responsive currents and slow decline of peak currents upon nomifensine administration were mainly due to the accumulation of DA concentration in fluids outside of cells, which is consistent with previous reports. (2,7,37) In a word, the above results indicated that amperometry coupled with Nafion/AuPt-alloy-nanoparticle-modified Au sites possessed sufficient feasibility for enabling in vivo recording of DA concentration in the brain of anesthetized rats.…”
Section: Da Recording In Striatum Of Anesthetized Ratsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, it was believed that the increased responsive currents and slow decline of peak currents upon nomifensine administration were mainly due to the accumulation of DA concentration in fluids outside of cells, which is consistent with previous reports. (2,7,37) In a word, the above results indicated that amperometry coupled with Nafion/AuPt-alloy-nanoparticle-modified Au sites possessed sufficient feasibility for enabling in vivo recording of DA concentration in the brain of anesthetized rats.…”
Section: Da Recording In Striatum Of Anesthetized Ratsmentioning
confidence: 81%
“…This factor is very important because major sources of interference, such as ascorbic acid (AA), also exist in body fluids together with DA and show very high concentrations with similar oxidization potentials to that of DA. Hence, a variety of composites, such as tyrosinase-based materials, (7) ion-exchange membranes, (8,9) conducting polymer films, (10) and molecularly imprinted polymer, (11) have been used to enhance the selectivity of DA detection. It is well known that the cation exchange polymer, Nafion, possesses the ability to repel negative ions and combine with positively charged species, because of the appearance of anionic sites in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…The current responses to the precursor of DA (L-DOPA) and DA metabolite (DOPAC) could be ascribed to their similar structure to DA and their interference were a common problem in electrochemical DA sensor systems. 35 It is apparently noted that L-DOPA and DOPAC could be interfere the sensor performance. However, their much lower sensitivities to the sensor and relatively lower concentration level in real samples 35 compared with the values of DA, could overcome this interference related limitation.…”
Section: Interference Studiesmentioning
confidence: 99%
“…35 It is apparently noted that L-DOPA and DOPAC could be interfere the sensor performance. However, their much lower sensitivities to the sensor and relatively lower concentration level in real samples 35 compared with the values of DA, could overcome this interference related limitation.…”
Section: Interference Studiesmentioning
confidence: 99%
“…11 An amperometric biosensor of dopamine using carbon fiber with tyrosinase has also been constructed. 12 A carbon fiber microcylinder modified with toluidine blue has been proposed to determine lactate dehydrogenase. 13 Chopped carbon fibers, which are an example of CFRPs, have been used as a reinforcing agent for thermoplastic resin.…”
Section: Introductionmentioning
confidence: 99%